1 - Normes africaines en matière de protection de l'environnement: by Laurent Zang - Laurent Zang, (Africa Development, 1998)
Since independence, African countries have recognised the existence of problems linked to environmental factors. This recognition is reflected in the international policy and cooperation in the sector. Several conventions and agreements signed between African states themselves and with other countries in the world have given birth to the formulation of international law to regulate the environment. The author, however, underlines the fact that Africa does not have the same environmental problems like Europe or the United States, owing to the status of the continent as underdeveloped, and castigates the tendency to use the continent as a dumping ground for toxic wastes. Using Cameroon as a case study, the author looks at the effectiveness of mechanisms put in place to stop environmental degradation and protect the flora, fauna and marine life, taking closer attention to industrial pollution, an often ignored danger to the environment on the continent.